The singular coupling limit for a simple pure number process - Waldenfels, Wilhelm von (Stochastics, 2012)
We consider the strongly continuous unitary one-parameter group W(t) on L2(R), which is related to the pure number quantum stochastic process restricted to the one-particle subspace L2(R).
Published online: 09 Jun 2011
Gesehen am 26.06.2018